Integrated optimisation design of a dynamic umbilical based on an approximate model. (July 2021) - Yang, Zhixun; Yan, Jun; Sævik, Svein; Lu, Qingzhen; Ye, Naiquan; Chen, Jinlong; Yue, Qianjin
Abstract: An optimised design of a dynamic umbilical requires an extreme cross-sectional stress to be maintained within an allowable limit and a fatigue life to be guaranteed to be sufficient. It should be noted that a dynamic umbilical is a typical geometric bi-scale structural system. It consists of a local cross-sectional scale and a global configuration scale, which are significantly different in terms of geometric sizes. In this study, we established an approximate model to achieve an optimised design of the dynamic umbilical by considering the parameters of local cross-sections and global configurations simultaneously. The design variables of a dynamic umbilical are independently identified and defined at both local sectional and global configuration scales in the approximate model. Furthermore, we selected the maximum tension strain and the maximum bending moment, for covering local and global properties, as the objectives to be minimised. The approximate model was observed to be effective in integrating the local and global responses into one loop so that the computational efficiency could be significantly increased. We implemented the optimisation framework on a dynamic umbilical with a lazy-wave configuration, which is considered to be a basis for a case study. Furthermore, we verified the feasibility and effectiveness of the integrated optimisation strategy by numerical simulations. Moreover, we compared the optimised dynamic umbilical properties with those without optimisation. It was observed that the fatigue life of the optimised dynamic umbilical was improved significantly, thereby indicating that the integrated optimisation methodology provides a new model and algorithm for an efficient design of the dynamic umbilical. Highlights: The challenges of designing cross section and global configuration of an umbilical are discussed. The design variables of local cross-section and global configuration of an umbilical are identified and defined. The integrated optimisation model of an umbilical based on an approximate model is established. The integrated optimisation methodology can give the optimal design with balance between rigidity and flexibility. The proposed integrated optimisation methodology is a means of making the design of an umbilical more efficient.